Antimicrobial efficacy of platinum‐doped silver nanoparticles. Issue 8 (3rd July 2020) - Wongkamhaeng, Kan; Wang, Junnan; Banas, Jeffrey A.; Dawson, Deborah V.; Holloway, Julie A.; Haes, Amanda J.; Denry, Isabelle
Abstract: Silver nanoparticles (AgNPs) have been proposed to combat oral infection due to their efficient ionic silver (Ag + ) release. However, concentrations required for antimicrobial efficacy may not be therapeutically viable. In this work, platinum‐doped silver nanoparticles (Pt‐AgNPs) were explored to evaluate their potential for enhanced Ag + release, which could lead to enhanced antimicrobial efficacy against S . aureus, P . aeruginosa, and E . coli . AgNPs doped with 0.5, 1, and 2 mol% platinum (Pt0.5 ‐AgNPs, Pt1 ‐AgNPs, and Pt2 ‐AgNPs) were synthesized by a chemical reduction method. Transmission electron microscopy revealed mixed morphologies of spherical, oval, and ribbon‐like nanostructures. Surface‐enhanced Raman scattering revealed that the surface of Pt‐AgNPs was covered with up to 93% Pt. The amount of Ag + released increased 16.3‐fold for Pt2 ‐AgNPs, compared to AgNPs. The initial lag phase in bacterial growth curve was prolonged for Pt‐AgNPs. This is consistent with a Ag + release profile that exhibited an initial burst followed by sustained release. Doping AgNPs with platinum significantly increased the antimicrobial efficacy against all species. Pt2 ‐AgNPs exhibited the lowest minimum inhibitory concentrations, followed by Pt1 ‐AgNPs, Pt0.5 ‐AgNPs, and AgNPs, respectively. Doping AgNPs with a small amount of platinum promoted the release of Ag +, based on the sacrificial anodic effect, and subsequently enhanced their antimicrobial efficacy.